Shared Leadership in Practice: When Does It Work Best? - Pearce, Craig L.; Wassenaar, Christina L. (Academy of Management, 2015)
Leadership is generally thought to flowfromthe top to the bottom in organizations. In fact, a cursory glance at the popularpress shows very clearly that top organizational leaders—the Chief Executive Officer orManaging Director—are often glorified as being the brains behind the success of the entire organization (e.g., Ray Kroc ofMcDonald’s, Bill Gates ofMicrosoft) or vilified as the cause of an organization’s downfall (e.g., Kenneth Lay of Enron). A look behind the scenes, however, shows a far more complex situation.
Craig L. Pearce (MEF Author)